2017
DOI: 10.1039/c6cp06658e
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazolylquinoxalines: novel fluorophores with tuneable sensitivity to solvent effects

Abstract: We report on the photophysical properties, conjugation, conformational behavior, intra- and intermolecular hydrogen bonds (HBs) of a series of novel fluorophores, consisting of 3-arylquinoxaline and benzimidazole moieties linked by a single CC bond. Computations employing density functional theory (DFT) reveal that conjugation between these moieties stabilizes syn-conformers with two HB centers located on the same side of the molecule. Anti-conformers form stronger intermolecular HBs with DMSO and DMF than syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…161 The study found that structural changes, for example, introduction of substituents to the para-positions of the aryl groups, or changing the substitution of the phosphorus atoms, can be used to tune the HOMO-LUMO gap of the molecules. TD-DFT and TDA-TD-DFT were also applied to the study of some fluorescent benzimidazolylquinoxaline derivatives, 162 finding good agreement between experiment and calculations using the PBE0 and B3LYP functionals.…”
Section: Simplified Tamm-dancoff Approximationmentioning
confidence: 89%
“…161 The study found that structural changes, for example, introduction of substituents to the para-positions of the aryl groups, or changing the substitution of the phosphorus atoms, can be used to tune the HOMO-LUMO gap of the molecules. TD-DFT and TDA-TD-DFT were also applied to the study of some fluorescent benzimidazolylquinoxaline derivatives, 162 finding good agreement between experiment and calculations using the PBE0 and B3LYP functionals.…”
Section: Simplified Tamm-dancoff Approximationmentioning
confidence: 89%
“…Benzimidazole and other azole derivatives raise much interest due to their luminescence properties, and as promising candidates for the development of sensors and solar cells [ 1 , 2 , 3 , 4 , 5 ]. They are receiving increasing attention due to their non-linear optical properties [ 6 , 7 ] and excellent thermal stability [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…38 In a recent contribution we have shown that quinoxalinones/quinoxalines possess interesting properties in this regard 39−46 and can be proposed as π-bridging fragments of NLO-phores 39−42 and as novel luminophores. 45,46 Indeed, due to their highly π-deficient character, these units can play a dual role acting simultaneously as electron-withdrawing (A) and π-bridging motifs in D-π-A structures. The extent of the conjugation induced by the presence of the π-bridge is indeed fundamental in modulating not only the optical properties of such compounds but also their response to external stimuli and in many instances their photophysical properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The role of the π bridge is fundamental to ensure an optimal electron mobility through the system, and hence, to optimize its functions, a broad range of aromatic heterocyclic moieties have been considered as π-linkers including thiazole, thiophene, phenothiazine, pyrrole, , and various diazines . In a recent contribution we have shown that quinoxalinones/quinoxalines possess interesting properties in this regard and can be proposed as π-bridging fragments of NLO-phores and as novel luminophores. , Indeed, due to their highly π-deficient character, these units can play a dual role acting simultaneously as electron-withdrawing (A) and π-bridging motifs in D-π-A structures. The extent of the conjugation induced by the presence of the π-bridge is indeed fundamental in modulating not only the optical properties of such compounds but also their response to external stimuli and in many instances their photophysical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation